Segmental Arterial Mediolysis with Supra-Aortic Vascular Involvement: Report of Two Cases - Jain, Vikash (Journal of Clinical Interventional Radiology ISVIR, 2019)
Segmental arterial mediolysis (SAM) is a rare noninflammatory vasculopathy predominantly involving the visceral arteries of the abdomen. The most common presentation described is massive intra-abdominal hemorrhage secondary to aneurysm rupture. In this report, we describe two cases with characteristic findings of aneurysm, dissection, and beading involving the visceral arteries and the supra-aortic vessels. SAM involving the supra-aortic vessels is extremely rare.
Keywords: segmental arterial mediolysis; dissection; aneurysm